Educational social policy and school violence: gaps in their attention - Cala-Montoya, Caridad (2020)
The present work sends a critical analysis to the Cuban educational social policy, in the treatment of school violence, with a view to its improvement and to make visible this problem. The proposed research takes triangulation as a methodological strategy and assumes the basic secondary education of the Santiago de Cuba municipality as empirical references for its development. From the analysis of the results it is highlighted that, although the country is on a clear path towards the visibility of this scourge, the nullity of the term in the ministerial decrees and resolutions of the educational policy favors its ignorance. In it, the tangential approaches to the subject are limited to students' antisocial behaviors and their contexts of vulnerability; leaving out the rest of the actors involved in its construction. Likewise, in the development of strategies for their attention, the alienating participation of retail groups distant from school reality tends to prevail, and they swarm fissures in the training guidelines that are implemented.